An investigation into the interaction partners of the scaffold protein human CNK1 in the NF-ÎºB pathway - Moodley, Holisha (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2019)
The protein connector enhancer of KSR1 (CNK1) plays a role in a number of signalling pathways including those involved in cell proliferation, cell growth and differentiation. De-regulation of these pathways has been linked to the promotion of oncogenic signalling. The involvement of CNK1 in all of these diverse pathways indicates a need to better understand the role of this protein within the cell and within key signalling networks. The research provides a platform to understand the intricate relationships that occur between these key signalling networks with the potential to identify new drug targets. CNK1 is multifunctional scaffolding protein that has binding domains that mediate and co-ordinate signalling within the MAPK, Hippo, PI3K/AKT, JNK and NF-ÎºB pathways as well as downstream of the AT2 receptor. The activity of CNK1 is regulated through its interactions with a range of different binding partners within these pathways. Of particular interest to this research is the role of CNK1 in NF-ÎºB signalling. The deregulation of the NF-ÎºB pathway is implicated in chronic inflammation, tissue damage and induction of cervical and breast cancer. CNK1 has been reported to regulate the non-canonical branch of the NF-ÎºB pathway, upstream of the IKK complex however new findings lead to uncertainty about these conclusions. In addition, the interacting partner of CNK1 in the NF-ÎºB pathway has not been elucidated. In this thesis, we aim to identify the binding partners of CNK1 in the NF-ÎºB pathway. First, we validate an epitope-tagged CNK1-expression construct to express elevated levels of CNK1 in cervical cancer cells. We report that the expression of myc-CNK1 is comparable to endogenous CNK1. Cells expressing elevated CNK1 levels were used in traditional co-immunoprecipitation reactions to identify potential CNK1-interacting proteins. We present data that indicates a potential role for NIK in the CNK1 signalling complex. We discuss the weaknesses of the traditional co-immunoprecipitation reactions and design an alternative co-immunoprecipitation technique with which to study CNK1-interacting partners. In this system, a promiscuous biotin ligase fused to the protein sequence for CNK1 (BirA-CNK1) is used to label proteins proximal to CNK1 with biotin. Using this BirA- CNK1-expressing construct in cervical cancer cells, we demonstrate that CNK1 interacts with IKKÎ±-IKKÎ² in the NF-ÎºB pathway.
Keywords: CNK1; Scaffold proteins